Domestic market research detecting the factors that influence consumer`s choice of meat products by domestic or foreign producers - Silovska nikolova, Aleksandra; Pejkovski Zlatko; Daniela Belichovska; Katerina Belichovska (Knowledge International Journal, 2019)
In order to gain their place on the market, meat producers need to produce meat products with high quality, which will be consistent in their quality, thus satisfying the consumers’ expectations. This was determined by the acquired results of our research. The most frequent crucial factor, when choosing meat product, is their sustainable quality, for which opt 145 (48,33%) examinees. The meat products quality is most frequent factor for 104 (34,67%) examinees, while 51 (17%) examinee feels that the crucial factor is price. Most of the examinees feel that meat both products by domestic and foreign producers, offered on the market are quality ones. However, generally, their opinion is that the domestic meat products have lower quality. The domestic meat processing companies need to focus on sustaining standard quality for meat products. The acquired results indicate that the majority of the examinees - 263 (87,67%) feel that the domestic meat products do not have consistent standard quality, whereas 199 (66,33%) examinees consider that the foreign meat products have consistent quality. Domestic meat processing companies need to pay more attention on quality management.
Keywords: meat products, quality, quality sustainability, consumer